How Burton Raffel Translated Chairil Anwar’s “Aku”: An Analysis in Poem Translation - Yohanes Maria Restu Dian Raharjo (Indonesian Journal of English Language Studies (IJELS), 2017)
The paper analyses the translation of Indonesian poem entitled “Aku” by Chairil Anwar, which is translated by Burton Raffel. The poem was written in 1943 and depicts the struggle of the natives of Indonesia to achieve independence from their colonizer. This paper wants to see how the poem is translated into English by a non-Indonesian who does not have social, cultural, or even historical background like Indonesian people. The focuses of the analysis are in the semantics and syntax as cultural and conceptual phenomena; the works of dynamic, pragmatic, equivalence; and the conveyance of ST message through the translation. Based on the analysis, it is found that the works of dynamic and pragmatic equivalence are needed in translating the poem because they can accommodate flexible relationship between the elements of SL and TL such as social and cultural concepts conveyed or depicted by the poem.